PENINGKATAN KEMAMPUAN MEMBACA DAN MENGHITUNG SISWA KELAS TINGGI DI SDI KENDA MELALUI TAMBAHAN JAM PELAJARAN - Fransiska Jaiman Madu; Asterius Juano; Mariana Jediut (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
Abstract: This research is motivated by the low aptitude of elementary student which is related to the learning materials in counting and reading in Kenda Public Elementary School. This study intends to describe the effectiveness of learning in additional time for the students who have low ability in counting and reading. The type of this research is using action research. That action is taken repeatedly and in every action is begun with the planning, giving treatment (action), observation, and reflection. Grounded on the upshot of this research, giving an additional hour of learning for the students who have difficulty in reading and counting could be narrated effective. This is shown in the grade that achieved by the students in every meeting, wherein the upgrading of giving treatment I, II, and III.